Design and Rationale of the Metastatic Renal Cell Carcinoma (MaRCC) Registry: A Prospective Academic and Community-Based Study of Patients With Metastatic Renal Cell Cancer. (28th May 2017) - Bhavsar, Nrupen A.; Harrison, Michael R.; Hirsch, Bradford R.; Creel, Patricia; Wolf, Steve P.; Samsa, Greg P.; Abernethy, Amy P.; Simantov, Ronit; Borham, Azah; George, Daniel J.
ABSTRACT: The Metastatic Renal Cell Cancer Registry, a large, nationally representative, prospective registry of patients with metastatic renal cell carcinoma (mRCC), aims to understand real-world treatment patterns and outcomes of patients with mRCC in routine clinical practice across the United States. This observational study is designed to enroll 500 patients with previously untreated mRCC from approximately 60 academic and community treatment sites; as of December 7, 2016, 500 patients have enrolled at 54 sites. Key endpoints include real-world data on reasons for treatment initiation and discontinuation; treatment regimens; disease progression; patient-reported outcomes; and healthcare resource utilization in this patient population.